A history of the German settlers in the Eastern Cape, 1857-1919 - Zipp, Gisela Lesley (Rhodes University, Faculty of Humanities, School of Languages, 2013)
This thesis came into being as the result of a question innocently posed to me three years ago: Why do some towns in the Eastern Cape have German names? This thesis is not so much an answer to that question (which is answered in the following paragraphs) as an attempt to answer the questions that followed: Were the Germans really as benevolent and hard-working as much of the most readily available literature implies? Why did the military settlers leave and the peasant farmer settlers remain? What was the nature of relationships between the German settlers and other groups in the area? How did the German settlers see themselves? The existing literature provides the historic details, more or less, but not the context and explanations I sought. As such, I set out to find them and document them myself, addressing three main questions: 1. What was the (changing) nature of the German settlers' day-to-day lives between 1857 and 1919? 2. How was a German identity maintained/constructed within the German communities of the Eastern Cape between 1857 and 1919? 3. How did the Germans interact with other groups in the area? In answering these questions, I have also provided the necessary background as to why these settlers chose to come to South Africa, and why some of them left. I have limited this study to the period between 1857 and 1919 so as to include the First World War and its immediate aftermath, a time when enmity between Great Britain and Germany would have made life difficult for German descendants in the Union of South Africa. Introduction, p. 7.
Keywords: Colonists -- Eastern Cape -- 19th Century; Immigrants -- Germany -- History; Immigrants -- Germany -- Social life and customs